運用Lee Shulman 教學推理與行動模式分析 國小教師國語教學知識之轉化 Applying Lee Shulman's Model of Pedagogical Reasoning and Action to Analyze the Transformation of Elementary School Teachers Teaching of Chinese Language Arts - 左榕 Jung Tso; 林意雪 Yih-Sheue Lin (National Changhua University of Education, 2023)
國語教學是奠定學生學習的基礎。然因國語教學內容龐雜，學科知識結構不確定，不易體察教學現場的複雜多變和解決教學問題。因此，本研究以Lee Shulman「教學推理與行動模式」為架構，透過互動取向質性研究方式，觀察四位國小教師經由教學轉化，建構學科教學知識（Pedagogical Content Knowledge, PCK）歷程。研究者並以個人實踐知識輔佐教師，藉由分析十二則教學案例，建構深化的「國語教學推理與行動模式」，作為檢核國語教學之工具。研究發現如下：一、國語教學須經「教學前教材轉化」、「教學中教法轉化」、「教學後省思」三階段，具循環遞迴（recursive）現象。其中的教學前教材轉化是教學推理與行動核心；教師教學重在「學習者」理解，且須隨時反省及改變策略；最後依據個案教學歷程，建構「國語教學推理與行動模式」。二、教師的學科內容知識、教學知識、學生特性知識是建構PCK 的關鍵；實踐知識有助於教學轉化；且教學轉化須植基於教師的基礎知識。三、教師先備知識、專家教師介入，及教材、學校文化因素，對教師教學推理與行動皆有影響。四、國語教學轉化須植基於「課文本位」（textbook-based）。因此建議教師須增強學科內容知識，透過「國語教學推理與行動模式」檢核教學，提升教學轉化能力，建構學科教學知識。 Chinese language arts build the foundation where students consolidate their learning, but, due to the complex contents of its teaching and the yet-to-be-discovered structure of subject knowledge, it is not easy to understand the complex and ever-changing nature of such teaching as well as to solve related teaching problems. In light of that, this qualitative research took an interactive approach to identify and understand four elementary school teachers' teaching transformation and their construction of pedagogical content knowledge (PCK) by using Lee Shulman's Model of Pedagogical Reasoning and Action as the theoretical structure. The researcher also provided assistance to the teachers with personal practice knowledge, coming up with twelve cases of their teaching to further facilitate the understanding of "pedagogical reasoning and action model for Chinese language arts teaching" and to evaluate the teaching of this subject. The research findings are as follows. 1. The teaching of Chinese language arts is recursive among three stages - the pre-teaching transformation of teaching materials, the during-teaching transformation of teaching methods, and the post-teaching reflection-among which the first one is the core of pedagogical reasoning and action. All four teachers have properly implemented their knowledge about the learners and were able to reflect and change their strategies at any time in terms of teaching. A "pedagogical reasoning and action model for Chinese language arts teaching" was established in accordance with these teaching cases. 2. The content knowledge, pedagogical knowledge, and knowledge of students' characteristics possessed by a teacher are extremely crucial in regards to the establishment of their PCK. Practice knowledge did help with teaching transformation whereas the teaching transformation must be based upon the teacher's basic knowledge. 3. Factors, such as prior knowledge of teachers, the intervention of expert teachers, teaching materials, and school culture, did influence the pedagogical reasoning and action of teachers. 4. The transformation of Chinese language arts teaching must be textbook-based. It is here for suggested that teachers should enhance subject content knowledge, check their teaching through the "pedagogical reasoning and action model for Chinese language arts teaching" to improve their teaching transformation ability, and construct pedagogical content knowledge.